Fluorosis in dairy COWS: Clinicopathological findings - SINGH, J L; SWARUP, D; DOGRA, R K S; SINGH, G R (The Indian Journal of Animal Sciences, 2013)
An outbreak of fluorosis was recorded In dairy cattle of Aarey Milk Colony, Bombay. Of the 638 cows, 88 manifested symptoms of hind limb lameness, reluctance to move, skeletal deformities, bony exostoses, and wasting of main mass of hind quarter and sholder muscles Slight to marked dental lesions,loss In milk production, Intermittent darrhoea and emaciation were also present. The affected cows had significantly high concentration of serum and urine fluoride, serum alkahne phosphatase, urea nitrogen and creatinine, and low haemoglobin content. Higher amount of fluoride In mineral mixture supplement (952.92Â±1 49 ppm) was suspected to be the principal source of excesive flouride.